2018
DOI: 10.1016/j.matbio.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor (CTGF) from basics to clinics

Abstract: Connective tissue growth factor, also known as CCN2, is a cysteine-rich matricellular protein involved in the control of biological processes, such as cell proliferation, differentiation, adhesion and angiogenesis, as well as multiple pathologies, such as tumor development and tissue fibrosis. Here, we describe the molecular and biological characteristics of CTGF, its regulation and various functions in the spectrum of development and regeneration to fibrosis. We further outline the preclinical and clinical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
220
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(229 citation statements)
references
References 243 publications
(232 reference statements)
8
220
0
1
Order By: Relevance
“…Data from previous studies have found tissue CTGF expression is upregulated in people with fibrotic diseases, including cirrhosis , cardiac fibrosis , crescentic glomerulonephritis , idiopathic pulmonary fibrosis , and systemic sclerosis . In addition, pharmacological blockade or genetic deletion of CTGF ameliorates the progression of fibrosis in various mouse organs . Together, these findings support the concept that adipose tissue fibrosis is involved in the pathogenesis of insulin resistance associated with obesity in humans, which has previously been demonstrated in rodent models .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Data from previous studies have found tissue CTGF expression is upregulated in people with fibrotic diseases, including cirrhosis , cardiac fibrosis , crescentic glomerulonephritis , idiopathic pulmonary fibrosis , and systemic sclerosis . In addition, pharmacological blockade or genetic deletion of CTGF ameliorates the progression of fibrosis in various mouse organs . Together, these findings support the concept that adipose tissue fibrosis is involved in the pathogenesis of insulin resistance associated with obesity in humans, which has previously been demonstrated in rodent models .…”
Section: Discussionsupporting
confidence: 83%
“…Connective tissue growth factor (CTGF) (also known as cellular communication network factor 2, CCN2) is a matricellular protein that is involved in regulating many biological processes, including fibrogenesis in multiple organs . Overexpression of CTGF increases ECM production, decreases ECM degradation, can cause fibrosis or enhance the susceptibility to fibrosis in lung, kidney, liver, and skin in mice .…”
Section: Introductionmentioning
confidence: 99%
“…CTGF is just the promoter of extracellular matrix. 21 VEGF can promote the growth of capillaries which could provide nutrition to extracellular matrix, thus, this cytokine is also the promoter of the extracellular matrix. 22 As VEGF is also a promoter of cancer 23 and β-elemene is an anticancer drug, whether there are other mechanisms for this drug to inhibit the expression of VEGF, needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of CTGF has already been described in fibrotic diseases of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w lung, liver and kidney amongst others (38). CTGF, as a matricellular protein, exerts its fibrotic effects through several mechanisms: binding to cell surface receptors and initiating signal transductions, binding to cytokines and mediating their binding to specific receptors, remodelling the extracellular matrix turnover and regulating the activity of cytokines and growth factors through signalling cross talks (39). Our data suggests that YAP/TAZ nuclear translocation, at least partially, drives CTGF activation.…”
Section: Discussionmentioning
confidence: 99%